The Influence of Social Media and Influencers on Purchase Decisions Through Product Purchase Interest on E-commerce Platforms (A Case Study at the Faculty of Economics and Business, UNJ 2025) - Effendi, Eliza Naza Maharani; Arumningtyas, Sekar Ayu; Usman, Osly (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study aims to examine the influence of social media and influencers on purchase decisions through purchase intention as a mediating variable (Case Study at the Faculty of Economics, Universitas Negeri Jakarta 2025). This research employs a quantitative method by collecting primary data through surveys distributed to students at the Faculty of Economics and Business, Universitas Negeri Jakarta, who have made purchases on e-commerce platforms. A sample of 121 respondents who had made purchases on e-commerce platforms was selected for the study. The responses gathered were analyzed using SmartPLS 4.0. The results of the hypothesis testing indicate that: 1) Social Media has an impact on Purchase Decisions, 2) Influencers affect Purchase Decisions, 3) Purchase Intention influences Purchase Decisions, 4) Social Media affects Purchase Decisions, 5) Influencers have an impact on Purchase Decisions through Purchase Intention, 6) Social Media affects Purchase Decisions through Purchase Intention, and 7) Influencers affect Purchase Decisions through Purchase Intention.